Dynamics of agriculture subject guides access at Kansas State University Libraries - Ramaswamy, Mohan; Haddock, Mike (My University, 2004)
The Internet has profoundly altered the way library users access information. Academic libraries have responded by creating library instruction tools and subject guides as web pages. Much effort has been invested in the development of web-based library guides. It has thus become increasingly important to study the level of subject guide access. Library website usage including subject guides access, forms a valuable output measure in contemporary library service evaluation. Accordingly, this study uses server statistics to analyze subject guide access in an academic science library. The potential use of this study is discussed.
Keywords: Web usage statistics; Academic libraries; Webliographies; Web server log; Use studies/Internet; subject guides